PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PEMBELAJARAN BAHASA INDONESIA MATERI TEKS EKSEMPLUM KELAS II SEMESTER 1 MTSN 1 ACEH UTARA TAHUN PELAJARAN 2017/2018 - Zakiyanti, Mutia (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2020)
This study aims to find out how the application of the Jigsaw Learning Model for the Exemplum Text material, as well as the improvement of student learning outcomes of Indonesian language learning material for the Exemplum Text for Students in Class IX / 2 Semester 1 MTsN 1 of North Aceh in the 2017/2018 academic year. This research is a research with a qualitative approach. The sample of this study amounted to 38 students. Data collection was carried out by means of Classroom Action Research stages. Based on the results of research data analysis, it is concluded that the application of the Jigsaw Learning Model to the Exemplum Text Material in Class IX / 2 MTsN 1 of North Aceh can actually improve student learning outcomes. The acquisition of student learning outcomes can be seen in the average class which shows an increase from cycle I to cycle II, the final result is above the minimum standard (76%), namely 90.5%. The improvement of student learning outcomes in the Exemplum Text material can also be seen from the results of teacher observations which show that with the implementation of the action in this study almost all students can master the Exemplum Text material properly. Before implementing the Jigsaw learning model as an effort to improve student learning outcomes. Where at the end of the cycle the results obtained in addition to this action can improve student learning outcomes of the exemplum text material, all students can also increase their interest and motivation in learning the exemplum text material.